Motivations and Barriers Associated With Physician Volunteerism for an International Telemedicine Organization - Kim, Erin J.; Fox, Steven; Moretti, Meghan E.; Turner, Michelle; Girard, Timothy D.; Chan, Stephen Y. (Frontiers in Public Health, 2019)
Introduction The Addis Clinic uses volunteer physicians to implement an international humanitarian telemedicine program. We sought to identify motivations and barriers that may contribute to physician volunteerism in international telemedicine. Methods We surveyed active and inactive volunteers working with The Addis Clinic. Descriptive statistics were used to examine closed-ended questions, while a qualitative approach identified overarching themes for open-ended questions. The Volunteer Functions Inventory framework was also applied. Results Among 69 active and 25 inactive volunteers, survey response rates of 74% and 72%, respectively, were attained. Volunteer cohorts exhibited comparable distributions across sex, marital status, and children. Active, as compared with inactive, participants were significantly more likely to be < 40 years old (51% vs. 39%, p = 0.01), have prior experience with international/global health (67% vs. 39%, p = 0.04), and express an interest in international/global health work (82% vs. 50%, p=0.008). Active volunteers were predominantly concerned with challenges regarding patient care: they more often reported the asynchronous nature of communication with FHWs as a significant barrier (37% vs. 6%, p = 0.047), and increased patient follow-up significantly drove their enthusiasm (64% vs. 35%, p = 0.05). Conversely, active volunteers were less likely to cite commitment/availability as a significant barrier for participation (33% vs. 72%, p = 0.002), less likely to be incentivized by opportunities to fulfill professional obligations (14% vs. 59%, p = 0.001), and more likely to be satisfied with the telemedicine experience (p<0.0001). Opportunities to receive remuneration or recognition did not increase the likelihood of volunteering for either cohort. Malpractice concerns were cited in a comparable minority across cohorts (20% vs. 17%). Conclusions Age and global health experience/interest were significant predictors of physician volunteerism. While inactive volunteers reported time commitment as a barrier, active participants were concerned with challenges regarding patient care and motivated by increased methods to connect with patients. Financial considerations and recognition were infrequently reported as a barrier. With advances in telemedicine globally, results from this study can be used by organizations involved in international telemedicine to develop effective volunteer recruitment and retention strategies.